Simulacra dalam Novel Hujan Karya Tere Liye (Tinjauan Postmodernisme Jean Baudrillard) - Elva, Elva; Tang, Muhammad Rapi (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
This study aims to reveal the simulacra model in Tere Liye's Rain novel, in terms of Jean Baudrilard's postmodernism. This research is descriptive qualitative in nature. The data in this study are in the form of words, phrases, sentences and paragraphs that contain models of simulacra. The source of data in this study is the novel Hujan by Tere Liye, published in Jakarta by Gramedia Pustaka Utama in 2016. The data in the study were analyzed using Jean Baudrillard's postmodernism theory. The data collection techniques used in this study were reading and note-taking techniques. Data analysis techniques are data reduction, data presentation, conclusion and verification. The results showed that the novel Hujan by Tere Liye found simulacra model. The simulacra model or form in the novel is in the form of pastiche or what is called pure imitation, parody is an allusion to an event, kitsch is identified with cheap art, and camp is a form or aesthetic without content.Â